Ultrastable MXene@Pt/SWCNTs' Nanocatalysts for Hydrogen Evolution Reaction. (8th May 2020) - Cui, Cong; Cheng, Renfei; Zhang, Hui; Zhang, Chao; Ma, Yonghui; Shi, Chao; Fan, Bingbing; Wang, Hailong; Wang, Xiaohui
Abstract: Developing nano‐ or atom‐scale Pt‐based electrocatalysts for hydrogen evolution reaction (HER) is of considerable importance to mitigate the issues associated with low abundance of Pt. Here, a protocol for constructing a hierarchical Pt––MXene–single‐walled carbon nanotubes' (SWCNTs) heterostructure for HER catalysts is presented. In the heterostructure, highly active nano/atom‐scale metallic Pt is immobilized on Ti3 C2 Tx MXene flakes (MXene@Pt) that are connected with conductive SWCNTs' network. The hierarchical heterostructure is constructed by filtrating a mixed colloidal suspension containing MXene@Pt and SWCNTs. Taking the advantages of the hydrophilicity and reducibility of MXene, the MXene@Pt colloidal suspension is prepared by spontaneously reducing Pt cations into metallic Pt without additional reductants or post‐treatments. The so‐fabricated hierarchical HER catalysts, in the form of membrane, show high stability during 800 h operation, a high volume current density of up to 230 mA cm −3 at −50 mV versus reversible hydrogen electrode (RHE) and a low overpotential of −62 mV versus RHE at the current density of −10 mA cm −2 . This solution‐processed strategy offers a simple, efficient, yet scalable approach to construct stable and efficient HER catalysts. Given the properties and the structure–activity relationships of the hierarchical Pt–MXene–SWCNTs' heterostructure, other MXenes probably show greater promise in HER electrocatalysis. Abstract : Hierarchical Pt–MXene–carbon nanotube (CNT) heterostructures in which Pt is 0D, MXene is 2D, and CNTs are 1D, are constructed by a simple, efficient, yet scalable solution method. The heterostructures enable high stability and low overpotential for hydrogen evolution reaction. This general strategy is expected to construct other hierarchical 0D/2D/1D heterostructures for high‐performance catalysts, sensors and so on.